Polymeric membranes grafted by ionizing radiation for uranium adsorption - Amanda Caroline Patricio Cardoso; Rafael Henrique Lazzari Garcia; Elita Fontenele Urano de Carvalho; Mohamad Al-Sheikhly; Yasko Kodama (Brazilian Journal of Radiation Sciences, 2024)
Fuel elements production by IPEN-CNEN has a perspective to be increased to attend Brazilian Multipurpose Reactor, under construction. This production generates liquid waste that requires proper treatment to minimize environmental impacts, promoting more sustainable practices. Considering the rise on nuclear power energy generation, and that there is global lack of terrestrial uranium sources, the increasing demand for this element has been leading to uranium exploit alternatives. So, several researches are available on uranium adsorption from sea water. Adsorption is one of process for removing metals from wastewater, due to its high selectivity and low environmental impact. Taking into account this scenary, in this study, Winged Polypropylene (WPP) fabric was grafted via ionizing radiation (RIG) with the monomer Bis[2-(methacryloyloxy) ethyl] phosphate (B2MP). RIG promotes functionalization of WPP with phosphate groups that are prone to capture U from solution. Synthesized WPP-g-polyB2MP membranes were characterized by Scanning electron microscopy (SEM), Raman spectroscopy, thermogravimetry and, uranium adsorption capacity by ICP-OES and gamma spectrometry. WPP-g-polyB2MP membranes were successfully synthesized by ionizing radiation grafting direct method. Reaction parameters, like reactants concentration, radiation absorbed dose, affected the degree of grafting (DoG). By physico-chemical characterization results it was possible to observe DoG differences with parameters variation. Optimization of these parameters was sought in order to achieve uranium adsorption, and to increase the adsorption capacity of the membrane.